Stop Bullying Sejak Dini : Edukasi dan Pendampingan melalui Sosialisasi di TBM Perma Curug Kota Serang - Mita Mita; TB Nurwahyu; Amelia Febriyanti; Syifa Hyatin Nufus; Muslihatun Amaliah; Ripahiyah Ripahiyah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Bullying is a social problem that can negatively impact children’s psychological well-being, emotional stability, and social development, especially if it is not identified and addressed at an early stage. Exposure to bullying during childhood may lead to long-term consequences such as low self-esteem, academic difficulties, social withdrawal, and even mental health issues. Therefore, preventive efforts are crucial to equip children with knowledge, awareness, and coping strategies. This community service activity was carried out through the Perma Curug Community Reading Garden (TBM) in Serang City with the primary goal of educating and supporting young children in preventing bullying. The methods used included interactive counseling sessions where children were introduced to the concept of bullying, its forms, and its harmful effects; educational games that helped children engage with the material in a fun and memorable way; and small group discussions that encouraged children to share their thoughts and experiences while practicing empathy and respect. The results of the activity indicated an increase in children’s awareness and understanding regarding the importance of respecting others, recognizing bullying behaviors, and the need to report or resist such actions. Moreover, the program also fostered a sense of togetherness and cooperation among participants. This initiative is expected to be a starting point for instilling anti-bullying values from an early age, while at the same time encouraging families, educators, and the wider community to actively contribute to creating a safe, supportive, and positive environment for children’s growth and development